2020
DOI: 10.1108/jmlc-06-2019-0047
|View full text |Cite
|
Sign up to set email alerts
|

Influence of justice, culture and love of money towards ethical perception on tax evasion with gender as moderating variable

Abstract: Purpose The purpose of this study is to evaluate the influence of justice, culture and love of money on ethical perceptions about tax evasion. As well as gender will strengthen the influence of justice, culture and love of money on ethical perceptions about tax evasion. Design/methodology/approach The primary data were collected and analyzed using a popular component-based model called partial least square (PLS). PLS consists of two sub-models, measurement model or outer model and structural model or inner m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 42 publications
1
10
0
17
Order By: Relevance
“…Faktor yang memengaruhi penerimaan pajak suatu daerah diantaranya adalah tingkat kepatuhan wajib pajak di daerah tersebut (Ariyanto, 2020) dan (Chau & Leung, 2009). Demi terciptanya target pajak yang diinginkan perlu ditingkatkan kepatuhan wajib pajak dalam melaksanakan kewajibannya (Doran, 2009).…”
Section: Nounclassified
“…Faktor yang memengaruhi penerimaan pajak suatu daerah diantaranya adalah tingkat kepatuhan wajib pajak di daerah tersebut (Ariyanto, 2020) dan (Chau & Leung, 2009). Demi terciptanya target pajak yang diinginkan perlu ditingkatkan kepatuhan wajib pajak dalam melaksanakan kewajibannya (Doran, 2009).…”
Section: Nounclassified
“…Helm and Mark (2012) showed that such a moderating variable is called potential moderation (homologiser moderation). Homologiser moderation indicates to variable that may potentially become a moderating variable influencing relationship between predictor (exogenous) and dependant variable (endogenous) (Ariyanto et al, 2020;Alshirah et al, 2020). One reason for the inconsistent results in the assorted studies is the possibility of the effect of a moderating variable.…”
Section: The Interaction Between Patriotism and Public Governance On Sales Tax Compliancementioning
confidence: 99%
“…Hasil penelitian tentang faktorfaktor yang mempengaruhi minat berwirausaha menunjukkan bahwa variabel minat berwirausaha dipengaruhi sebesar 60,4% secara total oleh modal, skill, tempat, dan jiwa kewirausahaan Muljaningsih, et al, (2012). Wirausaha merupakan orang yang menciptakan sebuah bisnis yang berhadapan dengan resiko dan ketidakpastian, yang bertujuan memproleh profit dan mengalami pertumbuhan dengan cara mengidentifikasi kesempatan dan memanfaatkan sumber daya yang diperlukan (Ariyanto, 2020). Motivasi untuk mengembangkan usaha baru diperlukan bukan hanya oleh rasa percaya diri dalam hal kemampuannya untuk berhasil, namun juga oleh kemampuannya untuk berhasil, dan juga oleh kemampuannya dalam mengakses informasi mengenai peluang kewirausahaan.…”
Section: Pendahuluanunclassified